Modal Identification of Dynamic Properties of the Cylindrical Grinder. - Pawłowski, Witold; Kępczak, Norbert (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2017)
In the paper the method of model identification of the cylindrical grinder dynamic properties by means of experimental modal test was described. The method application, hardware solution as well as the procedure of carrying out the identification modal test of the cylindrical grinder was presented. The experiment was performed in order to acquire the frequency response function (FRF) of the cylindrical grinder. Having obtained the experimental FRF, the mathematical model of the response function was created. That mathematical model of the machine tool dynamic behavior can be applied in grinder and grinding holistic model. The conclusions regarding the application aspects of experimental modal analysis in order to identify dynamic properties of the machine tool were drawn.
Keywords: experimental modal analysis; grinding process; modal identification; eksperymentalna analiza modalna; proces szlifowania; identyfikacja modelu